Biodegradation of crude oil and oil spill Plume Modeling of locally isolated beneficial microorganisms (2018)
A biodegradation study was performed to assess the biodegradation of crude oil by five locally isolated beneficial microorganisms (LIBeM) which were Candida tropicalis RETL-Cr1, Pseudomonas aeruginosa BAS-Cr1, Chromobacterium valaceum MAB-Cr1, Stenotrophomonas maltophilia RAS-Cr1 and Aeromonas hydrophila RETLCr3, as single and consortia cultures. Sabah Light Crude Oil was used as sole carbon source for all sets of experiments. The study was carried out using shakeflask culture at optimum temperature (30C to 37C), agitated at 200rpm. Microbial growth profile was monitored by measuring the optical density (O.D.600) on interval time. Biodegradation rate and efficiency were quantified by comparing the initial and final crude oil concentration, whereas the degradation of selected aliphatic hydrocarbons was quantified by comparing the initial and final area in chromatogram. The biodegradation ratios were monitored using Gas Chromatography-Mass Spectrometry (GC-MS). Present finding showed that all single and consortia culture able to grow in 5%, 10% and 15% (v/v) crude oil. The growth of all single species and consortia culture in crude oil proceed even after 70 days of the study. In 5% (v/v) crude oil, consortia culture has the highest biodegradation efficiency with overall biodegradation efficiency is 96.11% and the overall biodegradation rate after 70 days is 7.84 g/L/d. In 10% (v/v) crude oil, consortia culture has the highest overall biodegradation efficiency and rate which are 96.04% and 9.55 g/L/d respectively. In 15% (v/v), consortia culture also has the highest overall biodegradation efficiency of 94.02% and overall biodegradation rate of 10.75 g/L/d. The reduction of hydrocarbons by all single species and consortia culture are varies. In 5% (v/v) crude oil, single culture C. tropicalis RETLCr1 showed almost 100% degradation of n-alkane (heptadecane). In 10% (v/v) crude oil, consortia culture degraded 98% of n-alkane (eicosane). Meanwhile, on 15% (v/v) crude oil, consortia culture degraded 96% n-alkane (heptadecane) after 70 treatment days. Ultimately, the biodegradation ratio shows that biodegradation of crude oil had taken place during the specified biodegradation study. It can be concluded that the potency of microbe as hydrocarbon degrader in descending order is as follows: Consortia (all five species) > C. tropicalis RETL-Cr1 > A. hydrophila RETL-Cr3 > C. valaceum MAB-Cr1 > S. maltophilia RAS-Cr1 > P.aeruginosa BAS-Cr1. Two spill simulations incorporating biodegradation rate constant of consortia culture were run using MIKE 21/3 OS model. The spills flow to North East and South West direction due to different metocean conditions. The heavy oil was visually affected by the biodegradation compared to semi-volatile and volatile oil with the arrangement k1 > k2 > k3 >kANBR for all simulations. Therefore, the hypothetical spills represent significant effect of biodegradation to total oil mass after 14 days.